Globe-LFMC, a global plant water status database for vegetation ecophysiology and wildfire applications - Yebra, Marta; Scortechini, Gianluca; Badi, Abdulbaset; Beget, María Eugenia; Boer, Matthias M.; Bradstock, Ross; Chuvieco, Emilio; Danson, F. Mark; Dennison, Philip; Resco de Dios, Victor; Di Bella, Carlos M.; Forsyth, Greg; et al. (Scientific data, 2019)
Globe-LFMC is an extensive global database of live fuel moisture content (LFMC) measured from 1,383 sampling sites in 11 countries: Argentina, Australia, China, France, Italy, Senegal, Spain, South Africa, Tunisia, United Kingdom and the United States of America. The database contains 161,717 individual records based on in situ destructive samples used to measure LFMC, representing the amount of water in plant leaves per unit of dry matter. The primary goal of the database is to calibrate and validate remote sensing algorithms used to predict LFMC. However, this database is also relevant for the calibration and validation of dynamic global vegetation models, eco-physiological models of plant water stress as well as understanding the physiological drivers of spatiotemporal variation in LFMC at local, regional and global scales. Globe-LFMC should be useful for studying LFMC trends in response to environmental change and LFMC influence on wildfire occurrence, wildfire behavior, and overall vegetation health. Design Type(s) database creation objective • cross validation objective • physiological process monitoring objective Measurement Type(s) moisture content trait Technology Type(s) digital curation Factor Type(s) geographic location • environmental feature Sample Characteristic(s) Earth (Planet) • United States of America • French Republic Machine-accessible metadata file describing the reported data (ISA-Tab format)